Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.4269/ajtmh.16-0719
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of Chikungunya in the French Caribbean Islands of Martinique and Guadeloupe: Findings from a Hospital-Based Surveillance System (2013–2015)

Abstract: Abstract.Chikungunya virus (CHIKV) emerged in the Caribbean island of Saint-Martin in December 2013. We implemented a hospital-based surveillance system to detect and describe CHIKV cases including severe forms of the infection and deaths in the islands of Martinique and Guadeloupe. A case was defined as a patient with a CHIKV laboratory confirmation cared for in a public hospital for chikungunya for at least 24 hours, and a severe CHIKV case was defined as a CHIKV case presenting one or more organ failures. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 23 publications
3
52
1
Order By: Relevance
“…CHIKV continues to cause disease in humans for which there remains no licensed treatment or vaccine (Alfaro-Toloza, Clouet-Huerta, & Rodríguez-Morales, 2015). A practical and comprehensive protocol is necessary for the diagnosis of cases that occur via travel to regions experiencing ongoing outbreaks (Davidas et al, 2018;Ng et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…CHIKV continues to cause disease in humans for which there remains no licensed treatment or vaccine (Alfaro-Toloza, Clouet-Huerta, & Rodríguez-Morales, 2015). A practical and comprehensive protocol is necessary for the diagnosis of cases that occur via travel to regions experiencing ongoing outbreaks (Davidas et al, 2018;Ng et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Blood investigations in the initial stages can show transient anaemia, leukopenia, lymphopenia, mild thrombocytopenia, raised liver enzymes and serum creatinine levels. 15,34 Chikungunya virus can be detected by the reverse transcription (RT) -PCR method from 0 to 7 days of infection, after which PCR detection becomes unreliable. 12 IgM becomes detectable in 5-10 days after the onset of infection; positivity is at a maximum after 3 weeks and it remains positive up to 2-3 months.…”
Section: Diagnosismentioning
confidence: 99%
“…We previously reported an in‐hospital mortality rate of 9.1% in a population of subjects aged 65 years or older with CVI , vs . only 4% in the overall population of subjects admitted to hospital for CVI . While data exist regarding mortality in the acute phase, there are no available data regarding the medium‐ to long‐term mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have identified age as a risk factor for death during the acute phase of infection [10,11]. It has been shown that older subjects more frequently present atypical or severe form than younger patients [7,10], although data remain sparse and results are sometimes contradictory [12]. We previously reported an in-hospital mortality rate of 9.1% in a population of subjects aged 65 years or older with CVI [13], vs. only 4% in the overall population of subjects admitted to hospital for CVI [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation